Factors influencing the satisfaction level of college students in China: Literature analysis based on grounded theory - Gu, Qiongying; Lu, Guodong (Frontiers in Psychology, 2023)
Student satisfaction is an important index for evaluating the quality of higher education and the competitiveness of colleges in China, and most of the current studies on the factors influencing the satisfaction level of colleges students adopt quantitative research methods. A qualitative analysis of 48 literatures on college students’ satisfaction was conducted using NVivo12 in this study. We found that the influencing factors of college students’ satisfaction in China are composed of seven dimensions: school reputation, school environment, personal improvement, organizational management, logistical support, teaching quality, and charges and subsidies. Among them, teaching quality, school environment, organizational management, and logistical support are the core categories. Furthermore, school reputation, school environment, organizational management, logistical support, teaching quality, and charges and subsidies are external factors, while personal improvement is an internal factor. To improve the satisfaction level of college students, the two dimensions of external and internal factors must be taken into account, with external factors being given more attention. This study not only expands the scope of scenarios to which the grounded theory has been applied, but also provides a reference for other scholars to conduct more in-depth empirical studies on college students’ satisfaction in Chinese colleges.